ChemInform Abstract: β‐Secretase (BACE1)‐Inhibiting C‐Methylrotenoids from Abronia nana Suspension Cultures. Issue 48 (2nd December 2014) - Park, Se‐Hoon; Yang, Eun‐Ju; Kim, Sang‐In; Song, Kyung‐Sik
Abstract A novel C‐methylrotenoid, abronione A (I), is isolated together with three known rotenoids.